Pharmacists’ Role in Medication Consultation of Outpatients Type 2 Diabetes - Thanh Hai, Nguyen; Khanh Linh, Can; Thi Hong Nhung, Luu; Xuan Bach, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2022)
This study aimed to evaluate the efficiency of pharmacists’ consultation about special dosage forms in diabetes outpatients at Ha Long Medical Center. Subjects and method: Diabetes type 2 patients were treated as outpatients and managed at Ha Long Medical Center between 01/3/2019 and 01/9/2019. This study is a prospective cohort study. Results: After the Pharmacist performs routine consulting duties, the percentage of patients with correct knowledge and appropriate use of insulin increased statistically (p<0.05). The proportions of patients who did not swallow whole tablets of Diamicron MR and Glucophage XR decreased significantly from 62.3% to 15.8% and from 56.6% to 15.9%, respectively. Conclusion: Pharmacists’ consultation plays a vital role in improving knowledge and use of special dosage forms in diabetes outpatient. Keyword : Medication counseling, modified release, insulin, diabetes. *     * Corresponding author.    E -mail address: haint@hup.edu.vn    https://doi.org/10.25073/2588-1132/vnumps.4360 This study aimed to evaluate the efficiency of pharmacists’ consultation about special dosage forms in diabetes outpatients at Ha Long Medical Center. Subjects and method: Diabetes type 2 patients were treated as outpatients and managed at Ha Long Medical Center between 01/3/2019 and 01/9/2019. This study is a prospective cohort study. Results: After the Pharmacist performs routine consulting duties, the percentage of patients with correct knowledge and appropriate use of insulin increased statistically (p<0.05). The proportions of patients who did not swallow whole tablets of Diamicron MR and Glucophage XR decreased significantly from 62.3% to 15.8% and from 56.6% to 15.9%, respectively. Conclusion: Pharmacists’ consultation plays a vital role in improving knowledge and use of special dosage forms in diabetes outpatient. Keyword : Medication counseling, modified release, insulin, diabetes. References [1] International Diabetes Federation, IDF Diabetes Atlas 9th Edition, 2019. [2] S. Ahmad, M. T. Osman et al., Education of Correct Insulin Injection Technique amongst Diabetic Patients: Outcome Study from Malaysia, International Journal of Medical Research & Health Sciences, Vol. 5, No. 6, 2016, pp. 198-205. [3] F. A. Sefidani, E. P. Riazi, Impact of Pharmacist Intervention on Appropriate Insulin Pen Use in Older Patients with Type 2 Diabetes Mellitus in a Rural Area in Iran, Journal of Research in Pharmacy Practice, Vol. 6, No. 2, 2017, pp. 114-119, https://doi.org/10.4103/jrpp.JRPP_16_151. [4] D. T. Hang, N. T. Hai, et al., Survey Onknowledge and Impacts of Medication Consultation in Diabetes Patients in Phuc Yen Region General Hospital, VNU Journal of Science: Medical and Pharmaceutical Sciences, Vol. 33, No. 2, 2017, pp. 85-93, https://doi.org/10.25073/2588-1132/vnumps.4076 (in Vietnamese). [5] Electronic Medicines Compendium (EMC), Diamicron 30 mg MR Tablets, https://www.medicines.org.uk/emc/product/1321/smpc, (accessed on: January 10th, 2019). [6] Electronic Medicines Compendium (EMC), Glucophage XR 500 mg Prolonged Release Tablets, http:// www.medicines.org.uk/emc/ medicine /20952 (accessed on: January 10th, 2019). [7] Electronic Medicines Compendium (EMC), Lantus SoloStar 100 units/ml Solution for Injection in a Pre-filled Pen, http://www.medicines.org.uk/emc/medicine/22447, (accessed on: January 10th, 2019). [8] Electronic Medicines Compendium (EMC), Mixtard 100 units/ml Solution for Injection in a Pre-filled Pen, http://www.medicines.org.uk/emc/medicine/21366 (accessed on: January 10th, 2019). [9] J. Jiajia, L. Qingqing, Insulin Pen Injection Technique Survey in Patients with Type 2 Diabetes in Mainland China in 2010, Current Medical Research and Opinion, Vol. 30, No. 6, 2014, pp. 1087-1093 , https://doi.org/10.1185/03007995.2014.895711. [10] N. T. Kien, Implemented the Pharmacist's Consultation in Using Insulin in Diabetes Outpatients at Dan Phuong District General Hospital, Master Thesis, Hanoi University of Pharmacy, 2020, pp. 49-50.